Creative Inquiry-Based E-Worksheet: A Way to Improve Student's Self-Efficiency and Scientific Communication Skills - Apriyani, Lisa; Distrik, I Wayan; Rosidin, Undang (Universitas Islam Negeri Raden Intan Lampung, 2022)
The ability of self-efficacy and scientific communication is part of the important skills in the 21st century that must be practiced in learning. This study aims to improve self-efficacy and scientific communication skills using a creative inquiry-based e-worksheet. This study uses research and development methods that contain four stages, namely preliminary studies, planning and development, field testing, and dissemination. The sample of this research is the 68 12th-grade students of SMA N 1 Airnaningan. After product validation, obtained an average of 80.00% and declared valid. The average score of students' positive responses to the e-worksheet is 94.44%. While the effectiveness of the e-worksheet in improving self-efficacy and scientific communication skills was obtained from the results of the pretest and posttest with the experimental class N-gain value greater than the control class and the effect size self-efficacy value of 1.19 and scientific communication ability of 2.17 with high category. It was concluded that the e-worksheet based on creative inquiry was effective in increasing students' self-efficacy and scientific communication skills.